2013
DOI: 10.1002/jctb.4203
|View full text |Cite
|
Sign up to set email alerts
|

Solar Fenton: from pilot to industrial scale application for polishing winery wastewater pretreated by MBR

Abstract: BACKGROUND: Depending on the nature of the pollutants and the level of contaminants, detoxification of various industrial effluents, as well as winery wastewater, might be difficult and/or even impossible to achieve by single conventional biological methods. In such cases, biological processes alone are not able to reach effluent standards for discharge into the environment, and therefore, a pretreatment or post-treatment is required. In this study, winery effluent already treated in a membrane bioreactor (MBR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…bench and pilot scale) and detailed knowledge for their upscaling is still missing. To the authors' knowledge only one industrial-scale application of an advanced chemical process for the treatment of winery effluents is currently available in the literature [22]. Figure 1 presents the number of journal publications regarding the winery wastewater treatment during the period 1995-2014.…”
Section: Processes Currently Applied For the Treatment Of Winery Wastmentioning
confidence: 99%
See 2 more Smart Citations
“…bench and pilot scale) and detailed knowledge for their upscaling is still missing. To the authors' knowledge only one industrial-scale application of an advanced chemical process for the treatment of winery effluents is currently available in the literature [22]. Figure 1 presents the number of journal publications regarding the winery wastewater treatment during the period 1995-2014.…”
Section: Processes Currently Applied For the Treatment Of Winery Wastmentioning
confidence: 99%
“…Solar photo-Fenton oxidation was also able to significantly remove the color (75±2.2%), as well as the toxicity towards D. magna (100%) and the phytotoxicity towards three plant species (L. sativum, S. alba and S. saccharatum) to values lower than 28% (in terms of plant growth inhibition). The application of the abovementioned combined process at pilot and industrial scale proved to be a very effective treatment of winery wastewater [22], lowering the concentration of organic pollutants in the effluent to values below that of the Cypriot discharge limits regarding urban wastewater (i.e.…”
Section: Aops As Post-treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, up to 75% are winery wastewaters. This means that for each litre of wine, 1–2 L of liquid effluent are obtained . Winery effluents generally present a high organic load and phytotoxicity, constituting an environmental danger if disposed directly to natural water courses or soils.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has also been observed that some pollutants contained in winery wastewaters, such as various recalcitrant high molecular weight compounds (e.g. polyphenols, tannins and lignins), not amenable to biological treatment, may also be characterized by high chemical stability and/or by a difficult complete mineralization (Ioannou et al 2014).…”
Section: Introductionmentioning
confidence: 99%